Mercedes and the moose test (B) - Diermeier, Daniel (London : SAGE Publications Ltd, 2017)
The case describes a crisis management situation faced by Mercedes-Benz, a division of Daimler-Benz AG. In 1997 Mercedes introduced a revolutionary new car, the A-class, Mercedes' first entry into the compact car segment. The A-class was positioned as an entry-level vehicle in the Mercedes line and represented Mercedes' attempt to grow beyond its core market. A few days after the car was officially introduced, it rolled-over during a test known as the "moose test" conducted by a Swedish journalist. The A-class's failed moose-test created extensive media coverage in Germany and other European countries, threatening the success of the A-class launch.
Originally published: Diermeier, D. (2004). Mercedes and the moose test (B). 5-403-755(B) Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Daimler-Benz Aktiengesellschaft; Automobile industry and trade -- Case studies; Automobiles -- Testing -- Case studies; New products -- Management -- Case studies